Contrast Effects in Backward Evaluative Conditioning: Exploring Effects of Affective Relief/Disappointment Versus Instructional Information - Green, Luke; Luck, Camilla; Gawronski, B.; Lipp, Ottmar (2019)
Past studies of backward evaluative conditioning (EC) have found an assimilation effect, in that neutral conditional stimuli (conditional stimulus [CS]) were found to acquire the valence of co-occurring unconditional stimuli (US). Recent studies employing a concurrent forward and backward conditioning paradigm with instructions suggesting a contrastive relation between the US and the backward CS have resulted in contrast effects, in that backward CSs acquired valence opposite to the US. The current research investigated whether these effects were in fact due to the instructions highlighting the contrastive relation between the US and CS, or whether affective relief/disappointment experienced at US offset could account for this result. Consistent with the hypothesized role of instructions, backward CS contrast effects occurred only when instructions highlighted the valence of the US and attributed control of that US to the CSs. In contrast to the affective relief/disappointment hypothesis, no backward CS contrast effects were found without such instructions.